Chondroblastoma Expresses RANKL by RNA In Situ Hybridization and May Respond to Denosumab Therapy. (December 2020) - Suster, David I.; Kurzawa, Pawel; Neyaz, Azfar; Jarzembowski, Jason A.; Lozano-Calderon, Santiago; Raskin, Kevin; Schwab, Joseph; Choy, Edwin; Chebib, Ivan; Deshpande, Vikram
Abstract : Lesions of bone featuring osteoclast-like giant cells comprise a diverse group of entities, including giant cell tumor (GCT) of bone, chondroblastoma, and aneurysmal bone cyst, among others. The receptor activator of nuclear factor-κB ligand (RANKL) has been implicated in the pathogenesis of GCT of bone and may play a role in the pathogenesis of other giant cell–rich lesions as well. In addition, RANKL inhibitors (denosumab) have also been shown to have some efficacy in treating some giant cell–rich lesions. Herein, we examine RANKL expression by RNA in situ hybridization in a total of 84 osseous lesions with a focus on chondroblastoma, GCT, fibrous dysplasia, and aneurysmal bone cyst. The lesions were tested for RANKL expression using a chromogenic RNA in situ hybridization assay. RANKL expression was identified in 24/25 (96%) GCT, 24/26 (92%) chondroblastomas, 6/7 (86%) aneurysmal bone cysts, and 3/16 (19%) patients with fibrous dysplasia. RANKL expression was statistically lower in chondroblastoma and aneurysmal bone cyst compared with GCT. RANKL reactivity in fibrous dysplasia was exclusively seen in the 3 cases with osteoclast-type giant cells. Our results indicate a high proportion of chondroblastomas, GCTs, and aneurysmal bone cysts express RANKL while reactivity in fibrous dysplasia is dependent on the presence of osteoclast-type giant cells. On the basis of the success of denosumab therapy for GCTs, our results indicate that it may be a potential therapeutic option in other primary osseous tumors. Abstract : Supplemental Digital Content is available in the text.